2010
DOI: 10.1002/humu.21356
|View full text |Cite
|
Sign up to set email alerts
|

Missense mutations in the sodium borate cotransporter SLC4A11 cause late-onset Fuchs corneal dystrophya

Abstract: Homozygous mutations in the Borate Cotransporter SLC4A11 cause two early-onset corneal dystrophies: congenital hereditary endothelial dystrophy (CHED) and Harboyan syndrome. More recently, four sporadic patients with late-onset Fuchs corneal dystrophy (FCD), a common age-related disorder, were also reported to harbor heterozygous mutations at this locus. We therefore tested the hypothesis that SLC4A11 contributes to FCD and asked whether mutations in SLC4A11 are responsible for familial cases of late-onset FCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
111
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 23 publications
0
111
1
4
Order By: Relevance
“…16,17 The SLC4A11 (solute carrier family 4, sodium borate transporter, member 11) mutations cause sporadic and familial late-onset FED. 8,18 Mutations identified in the COL8A2, ZEB1 and SLC4A11 genes account for a small number of FED cases. Furthermore, four chromosomal loci are associated with late-onset FED, but the causative genes remain to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The SLC4A11 (solute carrier family 4, sodium borate transporter, member 11) mutations cause sporadic and familial late-onset FED. 8,18 Mutations identified in the COL8A2, ZEB1 and SLC4A11 genes account for a small number of FED cases. Furthermore, four chromosomal loci are associated with late-onset FED, but the causative genes remain to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Late-onset classic FECD can either be familial or sporadic, with an onset typically occurring after the age of 40 years. Although mutations in the zinc-finger E-box binding homeobox 1 (ZEB1) gene 6,7 and the solute carrier family 4 member 11 (SLC4A11) gene 8,9 have been reported as causative of late-onset FECD, these mutations were only rarely observed in the patient population. On the other hand, Baratz et al 10 reported that a genome-wide association study (GWAS) revealed a highly significant association between single nucleotide polymorphisms in transcription factor 4 genes (TCF4) in classic late-onset FECD.…”
mentioning
confidence: 99%
“…Mutations within SLC4A11 have been associated in humans with the development of both recessive and dominant corneal endothelial dystrophies [3,4,5,17] as well as recessive Harboyan syndrome presenting as congenital hereditary endothelial dystrophy with sensorineural deafness [2]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, heterozygous missense SLC4A11 mutations have been identified in a subset of patients with dominantly inherited late-onset Fuchs' endothelial corneal dystrophy (FECD4, OMIM No. 613268) [4,5]. …”
Section: Introductionmentioning
confidence: 99%